Grateful american ebook A journey from self to service. - Sinise, Gary (2019)
Discover the moving, entertaining, never-before-told story of how one man found his calling: to see that those who defend this country and its freedoms are never forgotten. As a kid in suburban Chicago, Gary Sinise was more interested in sports and rock 'n' roll than reading or schoolwork. But when he impulsively auditioned for a school production of West Side Story, he found his true purpose—or so it seemed. Within a few years, Gary and a handful of friends created what became one of the most exciting and important new theater companies in America. From its humble beginnings in a suburban Chicago church basement and eventual move into the city, the Steppenwolf Theatre Company launched a series of groundbreaking productions, igniting Gary's career along with those of John Malkovich, Joan Allen, Gary Cole, Laurie Metcalf, Jeff Perry, John Mahoney, and countless others. Television and film came calling soon after, and Gary starred in Of Mice and Men (which he also directed) and The Stand before taking the role that would change his life in unforeseeable ways: Lieutenant Dan in the Academy Award-winning Forrest Gump. The military community's embrace of the character of the disabled veteran was matched only by the depth of Gary's realization that America's defenders had not received all the honor, respect, and gratitude their sacrifices deserve. In the aftermath of the September 11 attacks, this became Gary's new calling. Grateful American, now a New York Times bestseller, documents Gary's dedication to working tirelessly on behalf of those who serve this country, sharing stories about how he has: Entertained more than a half million troops around the world playing bass guitar with his Lt. Dan Band Raised funds on behalf of veterans Founded the Gary Sinise Foundation with a mission to serve and honor America's defenders, veterans, first responders, their families, and those in need Grateful American is the moving, entertaining, profoundly gripping story of how one man found his life's work: to see that those who defend this country and its freedoms are never forgotten. Praise for Grateful American: "Gary Sinise writes as he lives, and as the artist and actor he has always been: with American authenticity, purpose, and a conviction that is inseparable from his nature." —Tom Hanks, actor and filmmaker "No entertainer alive today has visited and performed more for our troops at veterans hospitals and military bases all over the world than Gary Sinise. For years his foundation has built 'smart homes' for our troops that were severely wounded in combat. The book is called Grateful American, and I promise that after you read it you will be grateful for what Gary has accomplished and contributed to our country. He's truly one of a kind." —Clint Eastwood, actor, director, producer, and musician